Cdc14 Early Anaphase Release, FEAR, Is Limited to the Nucleus and Dispensable for Efficient Mitotic Exit - Yellman, Christopher M. (PLoS One, 2015)
Cdc14 phosphatase is a key regulator of exit from mitosis, acting primarily through antagonism of cyclin-dependent kinase, and is also thought to be important for meiosis. Cdc14 is released from its sequestration site in the nucleolus in two stages, first by the non-essential Cdc Fourteen Early Anaphase Release (FEAR) pathway and later by the essential Mitotic Exit Network (MEN), which drives efficient export of Cdc14 to the cytoplasm. We find that Cdc14 is confined to the nucleus during early mitotic anaphase release, and during its meiosis I release. Proteins whose degradation is directed by Cdc14 as a requirement for mitotic exit (e.g. the B-type cyclin, Clb2), remain stable during mitotic FEAR, a result consistent with Cdc14 being restricted to the nucleus and not participating directly in mitotic exit. Cdc14 released by the FEAR pathway has been proposed to have a wide variety of activities, all of which are thought to promote passage through anaphase. Proposed functions of FEAR include stabilization of anaphase spindles, resolution of the rDNA to allow its segregation, and priming of the MEN so that mitotic exit can occur promptly and efficiently. We tested the model for FEAR functions using the FEAR-deficient mutation net1-6cdk. Our cytological observations indicate that, contrary to the current model, FEAR is fully dispensable for timely progression through a series of anaphase landmarks and mitotic exit, although it is required for timely rDNA segregation. The net1-6cdk mutation suppresses temperature-sensitive mutations in MEN genes, suggesting that rather than activating mitotic exit, FEAR either inhibits the MEN or has no direct effect upon it. One interpretation of this result is that FEAR delays MEN activation to ensure that rDNA segregation occurs before mitotic exit. Our findings clarify the distinction between FEAR and MEN-dependent Cdc14 activities and will help guide emerging quantitative models of this cell cycle transition.